Curriculum Innovation in Vietnam: A Study on Teachers’ Attitudes using the Dimensions of ACB (Affective, Cognitive and Behavioral) Model (Journal of Contemporary Educational Policies and Practices, 2022)
This study examines teachers’ attitudes towards curriculum innovation in Vietnam. The paper attempts to contribute to understanding teachers’ attitudes and responses towards curriculum innovation by identifying that in terms of competencies, several affective, cognitive, and behavioral abilities of teachers may affect the overall attitudes towards curriculum innovation, which has extensive ramifications for the success of an educational project. To understand the attitude of teachers, a mixed-method explanatory sequential design approach is used. The authors collected quantitative data and then designed a qualitative open-ended plan to build upon the quantitative research. ANOVA was performed to test the statistical significance and correlations were established. Data gathered from interviews were analysed using thematic analysis. This study shows that the overall attitudes of teachers and educators towards curriculum innovation in Vietnam are favourable. However, both quantitative and qualitative analysis show there are certain challenges about such innovation. No teacher had either a broad view of curriculum innovation or awareness of the interrelationship between the three dimensions of attitude and the implementation of the curriculum although aspects of each dimension were mentioned by individual teachers.
Keywords: Curriculum innovation; competencies; experience; knowledge; policy makers; Vietnam